EFEKTIVITAS SIMULASI TELEHEALTH TERHADAP KETERAMPILAN KOMUNIKASI KLINIS MAHASISWA FISIOTERAPI PADA KASUS PENYAKIT MUSKULOSKELETAL - Pasaribu, Ida Aryani; Pasaribu, Dewi Astuti (Indonesian Trust Health Journal, 2025)
Musculoskeletal disorders are among the major public health problems in Indonesia, with a high prevalence and significant impact on quality of life. This condition requires physiotherapists to possess comprehensive clinical communication skills to support professional practice. The rapid development of digital health services has encouraged the adoption of telehealth simulation as an innovative learning approach. This study aims to evaluate the effectiveness of telehealth simulation in improving the clinical communication skills of physiotherapy students. A quasi-experimental design with a pretest–posttest control group was employed, involving 60 final-year physiotherapy students who were divided into an intervention group (n=30) and a control group (n=30). The instrument used was the Objective Structured Clinical Examination (OSCE) based on the Calgary-Cambridge Guide, which assessed four domains of communication: building rapport, gathering information, explaining and planning, and closing the session. Data were analyzed using the Wilcoxon Signed Rank Test to compare pretest and posttest scores within groups, and the Mann–Whitney U Test to compare between groups, with a significance level of p<0.05. The results indicated significant improvements in all communication domains in the intervention group (p<0.001), while the control group showed limited progress. The Mann–Whitney U Test confirmed significant posttest differences in all communication domains, favoring the intervention group (p<0.001). In conclusion, telehealth simulation is proven effective as an innovative learning strategy to enhance physiotherapy students’ clinical communication skills, and it is highly relevant for integration into physiotherapy curricula in the era of digital health transformation. Abstrak Gangguan muskuloskeletal merupakan salah satu masalah kesehatan utama di Indonesia dengan prevalensi tinggi dan berdampak signifikan terhadap kualitas hidup. Kondisi ini menuntut fisioterapis memiliki keterampilan komunikasi klinis yang komprehensif dalam menunjang praktik profesional. Perkembangan teknologi kesehatan mendorong penggunaan simulasi berbasis telehealth sebagai pendekatan pembelajaran inovatif. Penelitian ini bertujuan untuk mengevaluasi efektivitas simulasi telehealth dalam meningkatkan keterampilan komunikasi klinis mahasiswa fisioterapi. Penelitian menggunakan desain quasi experiment pretest–posttest control group dengan total 60 mahasiswa fisioterapi tingkat akhir yang dibagi ke dalam kelompok intervensi (n=30) dan kelompok kontrol (n=30). Instrumen yang digunakan adalah Objective Structured Clinical Examination (OSCE) berbasis Calgary-Cambridge Guide yang menilai empat domain keterampilan komunikasi: building rapport, gathering information, explaining and planning, closing the session. Analisis data dilakukan menggunakan Wilcoxon Signed Rank Test untuk perbandingan pretest–posttest dalam kelompok dan Mann–Whitney U Test untuk perbandingan antar kelompok, dengan tingkat signifikansi p<0,05. Hasil penelitian menunjukkan peningkatan signifikan pada kelompok intervensi di seluruh domain keterampilan komunikasi (p<0,001), sedangkan kelompok kontrol hanya mengalami peningkatan terbatas. Uji Mann–Whitney menunjukkan perbedaan signifikan pada seluruh domain komunikasi klinis saat posttest dengan skor lebih tinggi pada kelompok intervensi (p<0,001). Dengan demikian, simulasi telehealth terbukti efektif sebagai strategi pembelajaran inovatif yang mampu meningkatkan keterampilan komunikasi klinis mahasiswa fisioterapi serta relevan untuk diintegrasikan dalam kurikulum pendidikan fisioterapi di era transformasi digital.